Readmission after neurosurgical intervention in epilepsy: A nationwide cohort analysis. (2nd December 2019) - Kwon, Churl‐Su; Agarwal, Parul; Subramaniam, Varsha; Dhamoon, Mandip; Mazumdar, Madhu; Yeshokumar, Anusha; Panov, Fedor; Ghatan, Saadi; Jetté, Nathalie
Abstract: Objective: Hospital readmissions result in increased health care costs and are associated with worse outcomes after neurosurgical intervention. Understanding factors associated with readmissions will inform future studies aimed at improving quality of care in those with epilepsy. Methods: Patients of all ages with epilepsy who underwent a neurosurgical intervention were identified in the 2014 Nationwide Readmissions Database, a nationally representative dataset containing data from roughly 17 million US hospital discharges. Diagnosis of epilepsy was based on International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM)–based case definitions. Neurosurgical interventions for epilepsy: resective/disconnective surgery, responsive neurostimulation/deep brain stimulation, vagus nerve stimulation, radiosurgery, and intracranial electroencephalography were identified using ICD‐9‐CM procedure codes. Primary outcome was all‐cause 30‐day readmission following discharge from the index hospitalization. Results: There were a total of 2284 index surgical admissions. Overall, 10.83% (n = 251) of patients following an index epilepsy surgery admission were readmitted within 30 days. Factors independently associated with 30‐day readmission for all epilepsy surgery admissions were: Medicare insurance ( P  < .01), discharge disposition that was not home ( P  < .01), higher Elixhauser comorbidity indexes ( P  < .01), longer length of stay ( P  < .01), and adverse events of surgical and medical care during index stay ( P  = .04). In the multivariate model, Medicare insurance (hazard ratio [HR] 1.81 [1.29‐2.53], P  < .01) and length of stay (HR 1.02 [1.01‐1.04], P  < .01) remained significant independent predictors for 30‐day readmission. The most common primary reason for readmissions was epilepsy/convulsions accounting for 22.85%. Significance: Our results suggest that careful management of postoperative seizures and discharge planning after epilepsy surgery may be important to optimize outcomes and reduce the risk of readmission, particularly for patients on Medicare.